Tales and Music (Training and Practice : Journal of Educational Sciences, 2017)
Legacy of Zoltán Kodály, Katalin Forrai and Klára Kokas authorizes its dedicated educators to expand and search for solutions and pedagogic methods, so the musical experience will help in making children's musical upbringing more efficient. The aim of our research is the examination of the effects of interactive occupations and teaching onto the development of personality. The main point of irregular occupations leaded by the musicians, lectures is the continuous dialogue between an adult and a child. I wish to report on the experiences of some 2400 lectures and the inferences, conclusions based on them. My conviction, that the interactive music lessons directed together with my fellow musicians make it possible for the kindergartener fancy, his fantasy, the putting forth of his intuitive abilities, the early recognition of the musical talent and its development.